Combustion synthesis of triangular and multifunctional ZnO1-xNx (x <= 0.15) materials - Mapa, Maitri; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
The preparation and characterization of multifunctional ZnO1-xNx (x <= 0.15) via a simple solution combustion method is reported. ZnO1-xNx exhibits visible light absorption, thermal stability, nanometer-/ micrometer-sized triangular particles, and catalytic properties. X-ray diffraction studies of ZnO1-xNx, demonstrate that the lattice oxygen in ZnO is replaced by nitrogen without any major change in the wurtzite structure; however, charge compensation occurs, because of interstitial Zn atoms, as well as oxygen vacancies. Microscopic studies reveal the dominance of nanometer- and micrometer-sized triangles of ZnO1-xNx. UV-visible and Raman spectra indicate a midgap state, derived from N 2p states, and direct Zn-N interaction, respectively. Secondary ion mass spectrometry studies show the presence of N and ZnN species in the bulk and support the direct Zn-N interaction. Electron paramagnetic resonance (EPR) studies indicate the presence of a small amount of defects. Photocatalytic decomposition of rhodamine B, and anisole acylation at room temperature, highlights the effectiveness of ZnO1-xNx to catalysis applications. The aforementioned multifunctional characteristics suggest that ZnO1-xNx might be used in place of conventional ZnO for better control and that it might be explored for further applications in catalysis and optoelectronics.